KAJIAN POTENSI DAN STRATEGI PENGEMBANGAN EKOWISATA DI DANAU MATANO KABUPATEN LUWU TIMUR SULAWESI SELATAN - Amran Achmad; Asrianny Asrianny; Astuti Amri; Nida' Sari Achmad; Andi Utami Batari Putri (PERENNIAL, 2020)
The aims of this study is to determine the strategy of tourism development in Matano Lake, East Luwu Regency South Sulawesi Province. The result of this study is expected to become a reference in management and development of ecotourism and empower local communities to improve their living standards. Data collection was carried out by direct observations of bio-physical and other supporting factors for ecotourism potency. In addition, deep interviews using questionnaire was also carried out to know the local people and government perception related to future ecotourism programs that could be applied in Matano Lake. Data analysis showed that there were 7 strategies that can be implemented for the development of ecotourism in Matano Lake, i.e. (1) to develop community-based ecotourism programs, (2) to develop potential of nature tourism in the area, (3) to undertake promotion programme and dissemination of information that are focused on nature-based tourism in Matano Lake for local people, (4) to increase involvement of managers, (5) to establish cooperation between all parties in the management area, (6) to recommend PT.Vale to involve in management area, such as to build infrastructure and equip facilities for eco-tourism and (7) to disseminate the development of ecotourism to the public.